Computational and numerical analysis of radiator with different tube structures and nano fluid as coolant. (2021) - Aravindkumar, N.; Vignesh, S.; Kumaran, P.; Nirmal Kumar, C.; Nithish Kumar, K.; Navin, B.
Abstract: At present cooling medium utilized in the water cooled systems are water or some equivalent of it. Subsequently these cooling medium have less thermal conductivity leading to lesser amount of dissipation of heat from cooling systems. To improvise it, we need to increase the surface area which makes the cooling systems heavier, increases the cost of material and also lodges superior space in vehicle. This shows the need of an alternative cooling medium in locomotive cooling system. Researchers are trying to use Nano fluid as a cooling medium in locomotive cooling systems and a better results are expected from it. Metal related nano particles have a better thermal conductivity compared to existing cooling mediums, this type of nano particle so if we mix these particles in base fluid then the resultant mixtures were expected to have improvised thermal conductivity than the base fluid. Thus, Nano fluid can be used as coolant in automobile radiators.